Examining the effects of corruption on public debt in Iraq from 2004 to 2020 - hathal , Dr-Amed hamid jumaah; Ismael , Dr-Maytham Elaibi (Manar Elsharq Journal for Management and Commerce Studies, 2025)
This paper assesses corruption effects on public debt Using GDP to Public Debt Ratio. The economic analysis method was used, along with Iraq’s corruption perceptions index and its ranking among countries. The study found, through a simple linear regression model using OLS estimators that the effect of corruption perceptions on public debt is negative, as an increase in the corruption perceptions index by one unit leads to an increase in public debt by 2.335. The study also demonstrated that government spending is positively correlated with domestic debt, and that unproductive government spending has an indirect effect on public debt. As government spending, particularly current spending, increases, it leads to a higher budget deficit and public debt.